Polyamide composite material as well as preparation method and application thereof

By adding porcelain-forming agent and zirconium hydroxide to the polyamide composite material, the problem of insufficient leakage resistance and trace resistance of black halogen-free flame-retardant polyamide materials is solved, and the material's leakage resistance and trace resistance are improved. , suitable for electronic and electrical products and new energy products.

CN119192834APending Publication Date: 2024-12-27KINGFA SCI & TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411541634.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing black halogen-free flame-retardant polyamide materials have shortcomings in their leakage resistance and traceability, especially the performance degradation caused by carbon black and aluminum diethyl phosphinate during processing.

Method used

By adding porcelain-forming agents and zirconium hydroxide to the polyamide composite material, the thermal conductivity and non-conductivity of the porcelain-forming agents hinder the formation of carbon paths, improving the leakage-resistant traceability of the material, and improving flame retardancy.

Benefits of technology

It has achieved good leakage resistance and flame retardancy in the applications of electronics and electrical and new energy fields, and is suitable for high-voltage connectors and other products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112931530000071
    Figure BDA0005112931530000071
  • Figure BDA0005112931530000081
    Figure BDA0005112931530000081
  • Figure BDA0005112931530000082
    Figure BDA0005112931530000082
Patent Text Reader

Abstract

The invention discloses a polyamide composite material as well as a preparation method and application thereof, and belongs to the field of high polymer materials. According to the polyamide composite material disclosed by the invention, aluminum diethylphosphinate and the synergistic flame retardant are added to form a flame-retardant system; the ceramic forming agent and the zirconium hydroxide are added, so that the tracking resistance of the material is improved by utilizing the synergistic effect of the ceramic forming agent and the zirconium hydroxide. The polyamide composite material has good tracking resistance and flame retardance, and is suitable for preparing electronic and electrical products, new energy products and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer materials, and in particular to a polyamide composite material and a preparation method and application thereof. Background Art

[0002] Halogen-free flame-retardant polyamide is widely used in the fields of electronics, new energy, etc. due to its excellent mechanical properties, electrical properties, low smoke and toxicity, and environmental protection. With the increase in market demand, the requirements for the weather resistance and tracking resistance of black halogen-free flame-retardant polyamide materials are constantly increasing. At present, black halogen-free flame-retardant polyamide materials often use carbon black as the black species (i.e., black colorant), and use aluminum diethylphosphinate and synergistic flame retardants to form a flame retardant system. Among them, carbon black is a polymer composed of carbon atoms, and its particles are arranged in clusters. This structure makes carbon black have a high specific surface area and porosity, and can adsorb a certain amount of organic matter. The addition of carbon black can effectively resist the erosion of oxides, acid rain, ultraviolet rays, etc. in the atmosphere and moisture, and maintain long-term stability, but it will cause a significant decrease in tracking resistance (such as CTI, IPT); aluminum diethylphosphinate is prone to produce acidic substances during processing, which affects the material's tracking resistance. Therefore, it is a great challenge to improve the tracking resistance of halogen-free flame-retardant polyamide black materials containing carbon black and aluminum diethylphosphinate. Summary of the invention

[0003] Based on the defects of the prior art, the purpose of the present application is to provide a polyamide composite material and a preparation method and application thereof, and the obtained polyamide composite material has good resistance to leakage tracking and flame retardancy.

[0004] In order to achieve the above objectives, in a first aspect, the present application provides a polyamide composite material comprising the following components in parts by weight:

[0005] 24-61 parts of polyamide resin;

[0006] 15-30 parts of aluminum diethylphosphinate;

[0007] 5-10 parts of synergistic flame retardant;

[0008] 2-10 parts of porcelain forming agent;

[0009] Carbon black 0.2-3 parts;

[0010] Zirconium hydroxide 0.2-0.6 parts.

[0011] The polyamide composite material is added with a ceramic agent. On the one hand, the ceramic agent has good thermal conductivity. In the leakage tracking test, the heat generated by the high voltage test can be derived, the decomposition of polyamide can be alleviated, and the carbonization speed during the test can be slowed down. On the other hand, the ceramic agent is non-conductive and is exposed to the carbon path formed by the high voltage test, which hinders the formation of the carbon path, thereby improving the material's resistance to leakage tracking. At the same time, the ceramic agent has good thermal conductivity and can also improve the material's flame retardancy; adding zirconium hydroxide is also beneficial to improving the material's resistance to leakage tracking. The inventor also found that the ceramic agent and zirconium hydroxide do not significantly improve the resistance to leakage tracking of other flame retardant systems. The system is only applicable to diethyl phosphinate aluminum flame retardant system. The polyamide composite material has excellent resistance to leakage tracking and flame retardancy under the joint action of the above-mentioned components at a specific content, and is suitable for application in industries such as electronics and electrical or new energy.

[0012] In this article, "carbon path" refers to the black carbon pattern formed by carbonization of the material surface due to high voltage when the test solution is dropped between two electrodes during the tracking test. Since the formed carbon is conductive, when the material between the electrodes is completely carbonized to form a carbon conductive path, a high current will be generated, which will cause the material to catch fire and fail.

[0013] The polyamide resin is 24-61 parts by weight, such as 24 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight or 61 parts by weight.

[0014] The aluminum diethylphosphinate is present in an amount of 15-30 parts by weight, such as 15 parts by weight, 17 parts by weight, 20 parts by weight, 22 parts by weight, 25 parts by weight, 28 parts by weight or 30 parts by weight.

[0015] The synergistic flame retardant is 5-10 parts by weight, such as 5 parts by weight, 5.5 parts by weight, 6 parts by weight, 6.5 parts by weight, 7 parts by weight, 7.5 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.5 parts by weight or 10 parts by weight.

[0016] The ceramic forming agent is 2-10 parts by weight, such as 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight or 10 parts by weight.

[0017] The carbon black is 0.2-3 parts by weight, such as 0.2 parts by weight, 0.5 parts by weight, 0.7 parts by weight, 1 part by weight, 1.2 parts by weight, 1.5 parts by weight, 1.7 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.5 parts by weight, 2.7 parts by weight or 3 parts by weight.

[0018] The zirconium hydroxide is 0.2-0.6 parts by weight, such as 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight, 0.5 parts by weight, 0.55 parts by weight or 0.6 parts by weight.

[0019] Preferably, the zirconium hydroxide is 0.28-0.52 parts by weight, such as 0.28 parts by weight, 0.30 parts by weight, 0.32 parts by weight, 0.34 parts by weight, 0.36 parts by weight, 0.38 parts by weight, 0.40 parts by weight, 0.42 parts by weight, 0.44 parts by weight, 0.46 parts by weight, 0.48 parts by weight, 0.50 parts by weight or 0.52 parts by weight, etc.

[0020] When the weight proportion of the zirconium hydroxide is in the range of 0.28-0.52, the material has better resistance to leakage tracking.

[0021] Preferably, the ceramic forming agent includes at least one of mica, kaolin, montmorillonite, wollastonite, silicon dioxide, silicon nitride, boron nitride and aluminum nitride. More preferably, the ceramic forming agent includes boron nitride. Compared with ceramic forming agents such as mica, kaolin, montmorillonite, wollastonite, silicon dioxide, silicon nitride and aluminum nitride, boron nitride has a better effect on improving the tracking resistance of the material.

[0022] Preferably, the microscopic shape of the boron nitride includes at least one of a rod-shaped, a spherical, and a hexagonal plate-shaped. More preferably, the ceramic-forming agent includes hexagonal plate-shaped boron nitride. Compared with rod-shaped boron nitride and spherical boron nitride, hexagonal plate-shaped boron nitride is beneficial to improving the material's resistance to leakage tracking.

[0023] Rod-shaped boron nitride can be prepared according to patent CN104071760A. The specific preparation method includes the following steps: sodium borohydride NaBH 4 、UreaCO(NH 2 ) 2 and organic matter are added to tetrahydrofuran and stirred to disperse. Among them, urea CO(NH 2 ) 2 Sodium borohydride NaBH 4 The molar ratio of organic matter to sodium borohydride NaBH 4 The molar ratio of sodium borohydride NaBH 4The ratio of tetrahydrofuran is (0.1-0.2):10mL, then heated at 120-190°C for 8-12 hours under closed conditions, cooled, and rotary evaporated to obtain a solid precursor, which is placed in a tube furnace, heated to 900-1200°C at a heating rate of 2-10°C / min under an inert atmosphere, sintered at a constant temperature for 9-12 hours, then cooled to 400-600°C, sintered in air for 4-6 hours, and then cooled. The resulting product is sequentially washed with water, solid-liquid separation, ethanol washing, solid-liquid separation, and solid precipitate is dried to obtain rod-shaped boron nitride. The organic matter can be selected from at least one of glucose, phthalic anhydride, mannitol hexaacetate, and methyl methylbenzene; the inert atmosphere can be selected from an atmosphere formed by protective gases such as ammonia, nitrogen, and argon, and the protective gas flow rate is 50-500mL / min. In addition, rod-shaped boron nitride can also be purchased commercially.

[0024] Preferably, the average particle size of the hexagonal boron nitride, the spherical boron nitride, the mica, the kaolin, the montmorillonite, the wollastonite, the silicon dioxide, the silicon nitride and the aluminum nitride is independently 1 to 5 μm. The average particle size of these ceramic forming agents can be measured by the following method: weigh 0.5 g of ceramic forming agent, add it to 20 mL of anhydrous ethanol, then add 3-4 drops of polyvinyl pyrrolidone as a dispersant, ultrasonicate at 600 W for 30 min, then take 2 mL and drop it into a quartz cuvette, place it in a laser particle size analyzer to measure Dv50, and then get the average particle size.

[0025] Preferably, the average length of the rod-shaped boron nitride is 3 to 8 microns, and the average aspect ratio is 2: 1-6: 1. The average length and average aspect ratio of the rod-shaped boron nitride are tested as follows: using a Leica microscope, magnified 300 times, randomly selecting 500 samples, measuring and calculating their average length and average aspect ratio.

[0026] Preferably, the relative viscosity of the polyamide resin is 1.8 to 4.2. The relative viscosity of the polyamide resin can be selected to be 1.8, 2.0, 2.5, 2.7, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2 or a range formed by any two of the above values.

[0027] The relative viscosity of the polyamide resin can be measured according to the following test method: According to standard ISO 307:2007, the relative viscosity of the polyamide at a concentration of 0.25 g / dL is measured in 98 wt. % concentrated sulfuric acid at 25±0.01°C.

[0028] Preferably, the polyamide resin comprises at least one of a condensation product of at least one dicarboxylic acid and at least one diamine, a condensation product of at least one aminocarboxylic acid and a ring-opening polymerization product of at least one cyclic lactam. More preferably, the polyamide resin comprises at least one of polyhexamethylene adipamide and polycaprolactam.

[0029] Preferably, the synergistic flame retardant includes at least one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate, melamine zinc polyphosphate, and zinc borate. More preferably, the synergistic flame retardant includes at least one of melamine polyphosphate and zinc borate to make the flame retardant property of the material better.

[0030] Preferably, the carbon black includes at least one of carbon black powder and nylon-based carbon black.

[0031] Preferably, the following components are further included in parts by weight: 15-40 parts by weight of glass fiber, and the glass fiber can be selected in 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight or 40 parts by weight.

[0032] Preferably, the glass fiber includes at least one of alkali-free glass fiber (ie, E glass fiber), high alkali glass fiber (ie, A glass fiber), special glass fiber (ie, S glass fiber), D glass fiber, medium alkali glass fiber (ie, C glass fiber), and quartz glass fiber. More preferably, the glass fiber includes alkali-free glass fiber.

[0033] The polyamide composite material described in the present application may contain common additives such as light stabilizers, antioxidants, lubricants, etc. without impairing the effects of the present application.

[0034] Preferably, the following components are further included in parts by weight: 0.3-1 part of light stabilizer and 0.3-1 part of antioxidant.

[0035] Preferably, the light stabilizer includes at least one of a benzotriazole ultraviolet absorber and a hindered amine light stabilizer. More preferably, the light stabilizer includes a benzotriazole ultraviolet absorber and a hindered amine light stabilizer, and the weight ratio of the benzotriazole ultraviolet absorber to the hindered amine light stabilizer is (0.5-2):1.

[0036] The molecular structure of benzotriazole UV absorbers contains multiple conjugated double bonds and aromatic rings, which can absorb UV radiation and reduce the damage of UV radiation to materials; hindered amine light stabilizers can inhibit photo-oxidative degradation reactions and prevent material discoloration by capturing free radicals, decomposing hydrogen and peroxides, and transferring the energy of excited molecules; when benzotriazole UV absorbers and benzotriazole UV absorbers are used in combination and the mass ratio of the two is within (0.5-2):1, the synergistic effect of the two on improving the weather resistance of the material is stronger.

[0037] Preferably, the antioxidant comprises at least one of a hindered phenol antioxidant, a phosphite antioxidant, a cuprous halide composite antioxidant and an antioxidant containing a benzophenone functional group compound.

[0038] Preferably, the following components are further included in parts by weight: 0.01-1 part of lubricant.

[0039] Preferably, the lubricant includes at least one of hydrocarbons, esters, alcohols, fatty acids, fatty acid amides and metal soaps.

[0040] Preferably, the mass fraction of the polyamide resin in the polyamide composite material is above 22%, such as 22%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or a range formed by any two of the above.

[0041] In a second aspect, the present application provides a method for preparing the polyamide composite material, comprising the following steps:

[0042] The component raw materials except glass fiber are mixed and fed into the screw extruder from the main feeding port, and the glass fiber is fed from the side feeding port, plasticized, melt-extruded, drawn, cooled, and pelletized to obtain a polyamide composite material.

[0043] Preferably, the screw extruder is a twin-screw extruder with a length-to-diameter ratio of 36:1 to 48:1, a screw speed of 300 to 800 rpm, a barrel temperature of each section independently ranging from 160°C to 250°C, and a die temperature of 230°C to 260°C.

[0044] In a third aspect, the present application provides an application of the polyamide composite material in electronic and electrical products or new energy products. For example, the polyamide composite material can be used to prepare new energy high-voltage connectors and energy storage connectors.

[0045] Compared with the prior art, the beneficial effects of this application are:

[0046] (1) The polyamide composite material of the present application is added with aluminum diethylphosphinate and a synergistic flame retardant to form a flame retardant system; a ceramic agent and zirconium hydroxide are added to improve the material's anti-tracking performance by utilizing the synergistic effect of the two.

[0047] (2) The polyamide composite material of the present application has good tracking resistance and flame retardancy under the combined effect of the various components in specific amounts, and is suitable for the preparation of electronic and electrical products, new energy products, etc. DETAILED DESCRIPTION

[0048] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.

[0049] The raw materials used in the following examples and comparative examples are as follows, and unless otherwise specified, they are all commercially available raw materials. In addition, the component raw materials used in each parallel experiment are all of the same kind.

[0050] Polyamide resin 1: PA66 U2501, relative viscosity 2.0, INVISTA Nylon Chemical (China) Co., Ltd.;

[0051] Polyamide resin 2: PA6 BL40H, relative viscosity 4.0, Sinopec Baling Petrochemical Co., Ltd.;

[0052] Aluminum diethylphosphinate: Exolit OP 1230, manufactured by Clariant International AG;

[0053] Synergistic flame retardant 1: Budit 3141, melamine polyphosphate, manufactured by BUDENHEIM IBERICA, SLU;

[0054] Synergistic flame retardant 2: Safire 400, melamine zinc polyphosphate, manufactured by HUBER ADVANCEDMATERIALS;

[0055] Synergistic flame retardant 3: ZB-503, zinc borate, manufactured by Anhui Yishitong Materials Technology Co., Ltd.

[0056] Glass fiber: ECS10-03-568H, alkali-free glass fiber, manufactured by China Jushi Co., Ltd.

[0057] Ceramic agent 1: PN02, hexagonal boron nitride, average particle size 2.82 μm, manufacturer: Zibo Jingyi Ceramic Technology Co., Ltd.

[0058] Ceramic agent 2: rod-shaped boron nitride, with an average length of 5.5 μm and an average aspect ratio of 5:1, prepared as follows: sodium borohydride NaBH 4 Powder, ureaCO(NH 2 ) 2 The powder and glucose were added to a polytetrafluoroethylene-lined reactor in a molar ratio of 20:10:1, 1 L of tetrahydrofuran was added, and the mixture was stirred for 30 minutes. The reactor was sealed and heated at 190°C for 10 hours. The reactor was then naturally cooled to room temperature (25°C, the same below). The precursor obtained in the reactor was evaporated at 40°C using a rotary evaporator to obtain a solid precursor. The solid precursor was placed in a tubular furnace, and ammonia was passed through at a gas flow rate of 50 mL / min. The temperature was gradually increased from room temperature to 1000°C at a heating rate of 2°C / min, and the mixture was sintered at a constant temperature for 10 hours. The mixture was then naturally cooled to 600°C, and air was passed through at a constant temperature for 4 hours at a gas flow rate of 70 mL / min. The mixture was then naturally cooled to room temperature. The obtained product was sequentially washed with water, centrifuged, washed with ethanol, and centrifuged. The solid precipitate was dried in a vacuum drying oven at 60°C for 6 hours to obtain rod-shaped boron nitride.

[0059] Ceramic agent 3: ML-BN-QW02, spherical boron nitride, average particle size 2 μm, Zhejiang Manli Nanotechnology Co., Ltd.

[0060] Porcelain-forming agent 4: mica powder, average particle size 2.7 μm, manufactured by Fujian Yanzhuang Material Technology Co., Ltd.

[0061] Porcelain-forming agent 5: GY680, kaolin, average particle size 2.5 μm, manufactured by Jiangyin Guangyuan Superfine Powder Co., Ltd.

[0062] Porcelain-forming agent 6: montmorillonite, average particle size 2.5 μm, obtained by passing DK32B of Zhejiang Fenghong New Materials Co., Ltd. through a 5000 mesh sieve;

[0063] Porcelain-forming agent 7: XYNFW-SA, wollastonite, average particle size 2.6 μm, manufactured by Xinyu Nanfang Wollastonite Co., Ltd.

[0064] Porcelain-forming agent 8: GY305, silicon dioxide, average particle size 2.6 μm, manufactured by Jiangyin Guangyuan Superfine Powder Co., Ltd.

[0065] Porcelain forming agent 9: Si 3 N 4 , silicon nitride, average particle size 1.95μm, manufacturer is Nangong Jiuxin New Material Technology Co., Ltd.;

[0066] Ceramic agent 10: AlN, aluminum nitride, average particle size 2 μm, manufactured by Forsman Technology (Beijing) Co., Ltd.

[0067] Carbon black 1: N54 / 1044, nylon-based carbon black, masterbatch, carbon black content 25wt.%, manufacturer: Xiamen Lianfeng Plastic Co., Ltd.;

[0068] Carbon black 2: MagiCab 1013F, carbon black powder, manufactured by Anhui Heiyu Pigment New Materials Co., Ltd.

[0069] Zirconium hydroxide: X-006, manufactured by Shandong Desheng New Materials Co., Ltd.

[0070] Light stabilizer 1: 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, commercially available;

[0071] Light stabilizer 2: poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-amino]-hexylidene-[4-(2,2,6,6-tetramethylpiperidinyl)-imino]}, commercially available;

[0072] Antioxidant: Antioxidant 1098, commercially available;

[0073] Lubricant: montan ester wax, commercially available.

[0074] The following embodiments and comparative examples all provide a polyamide composite material, comprising the following steps: mixing the component raw materials except glass fiber and feeding them into a twin-screw extruder from the main feeding port, and feeding the glass fiber from the side feeding port of the sixth screw barrel, plasticizing, melt-extruding, drawing, cooling, and pelletizing to obtain a polyamide composite material, wherein the aspect ratio of the twin-screw extruder is 48:1, the screw speed is 450pm, the temperature of zone 1 is 185°C, the temperature of zone 2 is 260°C, the temperature of zone 3 is 275°C, the temperature of zone 4 is 280°C, the temperature of zone 5 is 280°C, the temperature of zone 6 is 280°C, the temperature of zone 7 is 275°C, the temperature of zone 8 is 275°C, the temperature of zone 9 is 275°C, and the temperature of the die head is 265°C.

[0075] The formulations of the polyamide composite materials of these embodiments and comparative examples are shown in Tables 1 and 2, and the following performance tests were performed on these polyamide composite materials:

[0076] Vertical combustion: injection molded 125*13*0.8mm burning specimens, tested their vertical combustion performance according to UL 94 standard, and recorded the first combustion time t of each sample 1 and the second burning time t 2 , the number of samples is 5, and the t of these 5 samples is counted 1 and t2 The sum is denoted as Σ(t 1 +t 2 );

[0077] Tracking resistance (IPT): Injection molded 130*50*3mm specimens were subjected to tracking resistance test according to ASTM D2303-2013. The constant voltage method was used, and the test voltage was 1kV and 1.5kV. The maximum voltage that passed the test was tested and recorded, where

[0078] The pass standard is: all five samples can last for more than 60 minutes, and the electrical trace on the material surface does not exceed 25mm.

[0079] The failure (NG) standard is: at least one of the five samples has a duration of less than 60 minutes or a surface trace of more than 25 mm;

[0080] Relative tracking index (CTI): tested according to IEC 60112-2020, sample size 100*100*3mm, sample quantity 5.

[0081] Table 1

[0082]

[0083]

[0084] Table 2

[0085]

[0086] From the above data, it can be seen that the materials in each embodiment have good tracking resistance and flame retardancy, such as CTI above 575V, IPT above 1kV, Σ(t 1 +t 2 ) is below 26s.

[0087] Comparison of Examples 1 and 6 to 14 shows that, compared with mica, kaolin, montmorillonite, wollastonite, silicon dioxide, silicon nitride, aluminum nitride, etc., using boron nitride, especially hexagonal boron nitride as a ceramic-forming agent is beneficial to improving the material's resistance to leakage tracking.

[0088] Compared with Examples 1 and 6 to 14, Comparative Example 1 did not add a porcelain-forming agent, and the thermal conductivity of the material was poor in the tracking test, and the polyamide was easily decomposed and carbonized, resulting in deviations in the material's tracking resistance and flame retardancy.

[0089] Comparison of Examples 1 to 5 with Comparative Example 2 shows that the addition of zirconium hydroxide is beneficial to improving the material's resistance to leakage current tracking; when 0.2-0.6 parts by weight of zirconium hydroxide is added, especially when 0.28-0.52 parts by weight of zirconium hydroxide is added, the material's resistance to leakage current tracking is better.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A polyamide composite material, characterized in that: It comprises the following components in parts by weight:

2. The polyamide composite material according to claim 1, characterized in that: The zirconium hydroxide is 0.28-0.52 parts by weight.

3. The polyamide composite material according to claim 1, characterized in that: The ceramic forming agent includes at least one of mica, kaolin, montmorillonite, wollastonite, silicon dioxide, silicon nitride, boron nitride and aluminum nitride.

4. The polyamide composite material according to claim 3, characterized in that: The ceramic forming agent includes boron nitride, and the microscopic shape of the boron nitride includes at least one of a rod shape, a sphere shape, and a hexagonal plate shape.

5. The polyamide composite material according to claim 3, characterized in that: The ceramic forming agent includes hexagonal boron nitride.

6. The polyamide composite material according to claim 1, characterized in that: The relative viscosity of the polyamide resin is 1.8-4.

2.

7. The polyamide composite material according to claim 1, characterized in that: At least one of the following conditions is met: S1. The polyamide resin comprises at least one of a condensation product of at least one dicarboxylic acid and at least one diamine, a condensation product of at least one aminocarboxylic acid and a ring-opening polymerization product of at least one cyclic lactam, and the polyamide resin preferably comprises at least one of polyhexamethylene adipamide and polycaprolactam; S2. The synergistic flame retardant comprises at least one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate, melamine zinc polyphosphate and zinc borate; S3. The carbon black comprises at least one of carbon black powder and nylon-based carbon black; S4. Also comprising the following components in parts by weight: 15-40 parts of glass fiber; S5. Also comprising the following components in parts by weight: 0.3-1 parts of a light stabilizer, 0.3-1 parts of an antioxidant; S6. Also contains the following components in parts by weight: 0.01-1 part of lubricant.

8. The method for preparing a polyamide composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The component raw materials except glass fiber are mixed and fed into the screw extruder from the main feeding port, and the glass fiber is fed from the side feeding port, plasticized, melt-extruded, drawn, cooled, and pelletized to obtain a polyamide composite material.

9. The method for preparing the polyamide composite material according to claim 8, characterized in that: The screw extruder is a twin-screw extruder with a length-to-diameter ratio of 36:1 to 48:1, a screw speed of 300 to 800 rpm, a barrel temperature of each section independently ranging from 160°C to 250°C, and a die head temperature of 230°C to 260°C.

10. Use of the polyamide composite material according to any one of claims 1 to 7 in electronic and electrical products or new energy products.

Citation Information

Cited By

  • Polyamide composite material as well as preparation method and application thereof

    CN121022094A